2012
DOI: 10.1101/gr.137885.112
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast genome-wide scan for SNP–SNP interactions in common complex disease

Abstract: Long-range gene-gene interactions are biologically compelling models for disease genetics and can provide insights on relevant mechanisms and pathways. Despite considerable effort, rigorous interaction mapping in humans has remained prohibitively difficult due to computational and statistical limitations. We introduce a novel algorithmic approach to find long-range interactions in common diseases using a standard two-locus test that contrasts the linkage disequilibrium between SNPs in cases and controls. Our u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
106
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 54 publications
0
106
0
Order By: Relevance
“…CACNA2D4 is part of the CACN gene family responsible for encoding voltagedependent calcium channels; its deletion was implicated recently in the risk for late-onset BP (21); another study showed it to interact significantly with another calcium subunit gene, RYR2, in BP (42). These genes are closely related to CACNA1A (whose direct association was not found in the current study), one of the genes more strongly associated with the risk of BP (64).…”
Section: Ica Derived Dmnsmentioning
confidence: 85%
See 1 more Smart Citation
“…CACNA2D4 is part of the CACN gene family responsible for encoding voltagedependent calcium channels; its deletion was implicated recently in the risk for late-onset BP (21); another study showed it to interact significantly with another calcium subunit gene, RYR2, in BP (42). These genes are closely related to CACNA1A (whose direct association was not found in the current study), one of the genes more strongly associated with the risk of BP (64).…”
Section: Ica Derived Dmnsmentioning
confidence: 85%
“…Interleukin family genes (IL3RA, IL-18, IL-12, IL-10, and IL1A/B/RA), representing a group of cytokines expressed in white blood cells, may play an important role in SZ (83,84). Although "regulation of smooth muscle contraction" was a top enriched pathway, upon examining the encompassed genes, they were primarily Ca 2+ channel/voltage regulation genes (including CACNA1C, CACNB2, and CACNA2D4), their strong interactors such as RYR2/3, and second-messenger molecules such as PKC and PLC-β1 that are crucial in smooth muscle contraction but also act as important cellular signaling molecules whose functions are linked strongly to psychiatric disorders (21,29,42).…”
Section: Ica Derived Dmnsmentioning
confidence: 99%
“…Studies such as these are able to ignore multiple-hypothesis correction issues due to their focus on known associated regions but do not have the potential to reveal novel loci. Other studies examining genomewide joint testing of all pairs of SNPs, including those with statistical interaction terms, pay such severe multiple-hypothesis correction penalties that many loci found via standard marginal approaches would not reach genome-wide significance (Prabhu and Pe'er 2012;Arkin et al 2014) and are computationally expensive, although effect methods for reducing the computational burden have been explored (Prabhu and Pe'er 2012;Wang et al 2015). Slavin and Elston (Slavin et al 2011) proposed testing all adjacent pairs and applied their approach in the Wellcome Trust Case Control Consortium (WTCCC) seven disease study.…”
mentioning
confidence: 99%
“…We then compute the difference in the average trait value between the two groups to determine whether the pair of SNPs is significantly associated with the trait. Finding an association between a trait and a pair of SNPs is called the ''pairwise association test,'' and recently, several different methods have been proposed for pairwise association tests (Evans et al, 2006;Zhang et al, 2010;Prabhu and Pe'er, 2012;Yang et al, 2009;Millstein et al, 2006;Ljungberg et al, 2004).…”
Section: Introduction Gmentioning
confidence: 99%
“…Most of these methods are only applicable to case/control data. These methods include TEAM (Zhang et al, 2010), which uses a dynamic programming approach to identify significant pairs, SIXPAC (Prabhu and Pe'er, 2012), which utilizes a novel randomization technique, BOOST (Wan et al, 2010), which utilizes a Boolean representation of data and a screening stage to filter out most nonsignificant SNP interactions, and RAPID (Brinza et al, 2010), which utilizes geometric properties of the v 2 statistic to identify significant pairs. However, none of these methods are applicable to quantitative traits.…”
Section: Introduction Gmentioning
confidence: 99%